From the history of conferences on the machine and mechanism science - Wojnarowski, Józef (Zielona Góra: Uniwersytet Zielonogórski)
In the course of the past sixty years of the Polish Committee for the Theory of Machines and Mechanisms (PC TMM) 24 scientific and didactic conferences have been held. The subject matter of these conferences, generally organized every other year, comprised problems of the classification, analysis and synthesis of mechanisms, the dynamics of machine systems, investigations concerning self-excited vibrations, the stability of the systems, the control of machines and biomechanics. The numbers of submitted papers as well as the number of participants substantiate the need of organizing such conferences, their importance and the activity of the Polish Committee of TMM for the purpose of creating a platform for the presentation and discussion of new research methods in the domain of mechanisms, machines, biomechanics and mechatronics.
Keywords: Scientific Conferences on TMM; Congresses of IFToMM; 15th World Congress in 2019